Agrotourism Tour Package Design at Persemaian Permanen Garahan (PPG) Cluster Durian Wisata Pinus Sidomulyo, Jember - Kusuma, Marchaenta Yogyanterra; Oktawirani, Panca (E-Journal of Tourism; Volume 11 Number 2 (September 2024), 2024)
The development of agritourism in Indonesia is one of the choices of tourist destinations. Agritourism is an alternative management for the promotion of tourism potential through attractions and activities that are attractive to visitors. Realizing its potential requires good management, one of which is the optimization of tourist attractions that are packaged into unique and attractive tour packages. The design of the Garahan Permanent Nursery Agrotourism Tour Package (PPG) Durian Cluster of Sidomulyo Pine Tourism in Jember Regency is a choice to package attractions and educational activities with plantation nuances that are full of natural beauty. Data collection is qualitative through interviews, observation, and documentation. The tour package applied to the Garahan Permanent Nursery Agrotourism (PPG) Durian Cluster Sidomulyo Pin Tourism gave rise to three types of tour packages, namely: Movie Tent, Sidomulyo Pinus Camp, and Sidomulyo Kidventures. The results of designing the packages are in the form of itinerary flyers and package brochures to be promoted using promotional media.